A Physiologically-Motivated Compartment-Based Model of the Effect of Inhaled Hypertonic Saline on Mucociliary Clearance and Liquid Transport in Cystic Fibrosis - Markovetz, Matthew R. (PLoS One, 2014)
BACKGROUND: Cystic Fibrosis (CF) lung disease is characterized by liquid hyperabsorption, airway surface dehydration, and impaired mucociliary clearance (MCC). Herein, we present a compartment-based mathematical model of the airway that extends the resolution of functional imaging data. METHODS: Using functional imaging data to inform our model, we developed a system of mechanism-motivated ordinary differential equations to describe the mucociliary clearance and absorption of aerosolized radiolabeled particle and small molecules probes from human subjects with and without CF. We also utilized a novel imaging metric in vitro to gauge the fraction of airway epithelial cells that have functional ciliary activity. RESULTS: This model, and its incorporated kinetic rate parameters, captures the MCC and liquid dynamics of the hyperabsorptive state in CF airways and the mitigation of that state by hypertonic saline treatment. CONCLUSIONS: We postulate, based on the model structure and its ability to capture clinical patient data, that patients with CF have regions of airway with diminished MCC function that can be recruited with hypertonic saline treatment. In so doing, this model structure not only makes a case for durable osmotic agents used in lung-region specific treatments, but also may provide a possible clinical endpoint, the fraction of functional ciliated airway.